Distribution and Determinants of Suspected Adverse Events among COVID like Illness (CLI) Patients with Different Comorbidities (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Several drugs were administered to patients with COVID-19, focusing on their antiviral, immunomodulatory, or anti-inflammatory actions, which could potentially present risk since most of these medicines have the potential to cause numerous adverse effects.Objective: This study aimed to observe the incidence of suspected adverse events of selected medicines among COVID-like ill (CLI) patients.Methodology: A prospective analysis was performed from February 15, 2021, to June 15, 2021, upon 223 CLI patients. CLI patients were enrolled from the National Institute of Diseases of the Chest and Hospital. The incidence of suspected adverse events were assessed among CLI patients, the laboratory investigations values of SGPT, RBS, serum electrolytes, and serum creatinine of day one and day five and interpreted the 12-lead ECG tracing paper of the same days assessed hepatotoxicity, nephrotoxicity, cardiotoxicity, and metabolic disorders.Results: The result showed the incidence of adverse events was 21.5% in CLI patients. Only the incidence of hepatotoxicity was more (12.55%) among CLI patients but statistically not significant (p > 0.05). In CLI patients who had co-morbidities, the incidence of adverse events was relatively less and only a significant difference was seen among diabetes mellitus patients (p ≤ 0.05).Conclusion: This study showed that the rate of adverse events was present in CLI patients when treated with the same specific drug of interest in addition to other medicines they received.Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):35-41